2015
DOI: 10.1002/qua.24873
|View full text |Cite
|
Sign up to set email alerts
|

Proton dissociation and transfer in hydrated phosphoric acid clusters

Abstract: The dynamics and mechanisms of proton dissociation and transfer in hydrated phosphoric acid (H3PO4) clusters under excess proton conditions were studied based on the concept of presolvation using the H3PO4–H3O+–nH2O complexes (n = 1–3) as the model systems and ab initio calculations and Born–Oppenheimer molecular dynamics (BOMD) simulations at the RIMP2/TZVP level as model calculations. The static results showed that the smallest, most stable intermediate complex for proton dissociation (n = 1) is formed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 59 publications
2
29
1
1
Order By: Relevance
“…Due to their ability to approximate the effects of electron correlations with reasonable computational resources, DFT methods have been widely used in computational chemistry research. However, because the accuracy of DFT depends on the types of interactions in the chemical systems, the applicability and performance of B3LYP/TZVP calculations were systematically examined in our previous work by benchmarking with the second‐order Møller–Plesset perturbation theory (MP2) method with the resolution of the identity (RI) approximation and the TZVP basis set (abbreviated RIMP2/TZVP). Because the key properties, for example, the H‐bond structures, interaction energies, and 1 H NMR and vibrational frequencies of the transferring protons obtained from both methods are comparable, B3LYP/TZVP calculations were applied in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to their ability to approximate the effects of electron correlations with reasonable computational resources, DFT methods have been widely used in computational chemistry research. However, because the accuracy of DFT depends on the types of interactions in the chemical systems, the applicability and performance of B3LYP/TZVP calculations were systematically examined in our previous work by benchmarking with the second‐order Møller–Plesset perturbation theory (MP2) method with the resolution of the identity (RI) approximation and the TZVP basis set (abbreviated RIMP2/TZVP). Because the key properties, for example, the H‐bond structures, interaction energies, and 1 H NMR and vibrational frequencies of the transferring protons obtained from both methods are comparable, B3LYP/TZVP calculations were applied in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Because this theoretical study focused on the dynamics of the structural‐diffusion process in the H‐bonds between the phosphonic acid‐functional groups, and our previous results showed that the intermediate complex that determines the rate of the proton‐exchange process is preferentially formed in excess proton conditions, both neutral and protonated PVPA (PV(PA) n and H + PV(PA) n , respectively, n = number of H 2 PO 3 functional groups) were tentatively chosen as model systems. The likelihood of proton exchange was anticipated primarily from the asymmetric stretching coordinate Δ d DA = | R OH – R O.H |, where R OH and R O.H are the OH and O.H distances in the OH.O Hbond, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations